WHERE DOES OUR DIALOGUE GO FROM HERE? - John B Chethimattam (Journal of Dharma, 1994)
It is very exciting today to look ahead into the twentyfirst century, from the long way we have come in our pilgrimage of interreligious dialogue. The first interreligious seminar I attended was held at Madras in December 1955. The theme of the seminar was "India and the Fullness of Christ" and the leading question was: What can Christianity Jearn from the Indian religions and what can Christianity contribute to India? We were then in the exclusivist mood: A Christian could not be a Hindu, and a Hindu is totally different from the Christian. J.N. Farquhar in his classical work "The Crown of Hinduism", published in 1913, had boasted that in the climax of world civilization all religions of the world had been weighed and all but Christianity had been found wanting. At a time of crisis the other religions based in human traditions would fall apart and Christianity alone could survive. World War I which began the very next year gave that boast a crude shock with the European Christian nations at the throat of each other.